(untitled) (Research, Society and Development, 2022)
Objective: To analyze national and international scientific production regarding the working and health conditions of health agents, from 2007 to 2017. Methodology: Integrative review of the working and health conditions of health agents, through an electronic search for articles indexed in the PUBMED, MEDLINE, SCIELO and LILACS databases, using the descriptors primary health care, occupational health, health personnel, community health workers, in english, from october to december 2017. After applying the inclusion and exclusion criteria and full reading 26 articles were part of this review, and were analyzed according to a standardized form, with data referring to authorship, journal, year of publication, population, objective and methodology. The extracted information was submitted to categorical content analysis. Results: There was a predominance of studies published in Brazil, in the state of São Paulo, with a quantitative approach. Of this material, 18 studies addressed health conditions and 15 pointed to risk factors at work. Among the inadequate conditions, they highlighted the difficulties imposed by living and working in the territory, environmental situations, exposure to solar radiation, violence and ergonomic risks. Work-related mental disorders among health workers were the most studied health problems, followed by skin problems, voice complaints and musculoskeletal system injuries. Conclusions: It was found that the working conditions and health of health agents point to the need for changes in work processes, in order to minimize potential negative effects on health, especially mental health.